2019
DOI: 10.1016/j.foodcont.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the synergistic antimicrobial effect of carvacrol and zinc oxide nanoparticles against Campylobacter jejuni

Abstract: Chapter 4: Investigation of the gene expression profile of Campylobacter jejuni after treatment with carvacrol and zinc oxide nanoparticles .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 123 publications
0
13
0
2
Order By: Relevance
“…Carvacrol is the major component of oregano and thyme essential oil [48]. Many studies have shown that the antibacterial effect of carvacrol against Gram-positive bacteria is stronger than that against Gram-negative bacteria, which may be because of the fact that the cell wall of Gram-negative bacteria is covered with a membrane containing lipopolysaccharide, limiting the diffusion of hydrophobic compounds through the membrane surface [49,50].…”
Section: Antibacterialactivitymentioning
confidence: 99%
“…Carvacrol is the major component of oregano and thyme essential oil [48]. Many studies have shown that the antibacterial effect of carvacrol against Gram-positive bacteria is stronger than that against Gram-negative bacteria, which may be because of the fact that the cell wall of Gram-negative bacteria is covered with a membrane containing lipopolysaccharide, limiting the diffusion of hydrophobic compounds through the membrane surface [49,50].…”
Section: Antibacterialactivitymentioning
confidence: 99%
“…Moreover, using the same dosage of Ag NPs (the TEM image is shown in Figure S1) prepared without stabilized ligand or supports led to a much lower inhibition effect on both gram-negative and gram-positive bacterial strains (Figure S3), probably due to their aggregations in the liquid. Obviously, the nanocomposite demonstrated much higher antibacterial efficiency than the single pure ZIF-8 and Ag Nps (shown in Figure 6), indicating that the copresence of Ag Nps and ZIF-8 provided a synergistic effect on its antibacterial activity [16,25]. As reported by Guo et al, they also observed that the core-shell Ag@ZIF-8 nanowires exhibited much higher antibacterial activities than pure Ag nanowires and ZIF-8 [16].…”
Section: Resultsmentioning
confidence: 82%
“…As shown in Figure 5 and Figure 6, in the control tests, the pure H-ZIF-8 show little antibacterial effect on both the gram-positive bacteria, S. aureus and gram-negative, E. coli strains. Many studies have shown that the released zinc ions from Zn-based nanomaterials and/or the attachment of nanoparticles or their aggregates to the organism were responsible for their nanotoxicity [25,26,27,28,29]. The Ag NP-decorated H-ZIF-8 progressively inhibited the growth of the organism and showed a significantly enhanced antibacterial property compared to the same dose of pure H-ZIF-8.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, carvacrol was combined with ZnO NP and this combination was found highly effective against Campylobacter jejuni . Moreover, it was also observed that a single treatment with one antibacterial agent, in low concentration, could show bacteriostatic effect [ 59 ]. The idea of combining essential oil with ZnO NP enabled us to use antibacterial agents in low concentrations to ensure biocompatibility.…”
Section: Discussionmentioning
confidence: 99%